Linguo-Conceptual Studies of Literary Text: Evolution of Theoretical and Methodological Approaches - I. V. Kononova; T. A. Pruczkikh (Дискурс, 2023)
Introduction. The  article  presents  the  results  of  an  analytical  review  of  scientific  papers reflecting  the  stages  of  formation  and  development  of  cognitive  poetics  as  an interdisciplinary  research  area  in  Russian  linguistics.  The  purpose  of  the  article  is  to systematize and critically analyze approaches, concepts and methodological principles of the study of concepts that constitute the cognitive basis of literary texts, authors’ idiostyles and, by extension, of poetic sociolects and literary genres.Methodology  and  sources. The  paper  reviews  theoretical  concepts  and  approaches (developed by R. Tsur, P. Stockwell, I.A. Tarasova, N.S. Bolotnova, L.O. Butakova, etc.), which served as the foundations of cognitive poetics. A comparative analysis of works focusing on the structure of literary concepts, their textual representation aspect and categorization criteria is carried out. The studies which concentrate on the application of corpus methods in order to analyze literary texts, including the works by B. Fischer-Starcke, D. Siepmann, A. Stefanowitsch, M. Mahlberg, etc., also formed the methodological basis for the analytical review.Results and discussion. As a result of the review study, the evolution of theoretical and methodological  approaches  to  literary  concepts  and  literary  texts’  ideospheres  is demonstrated. The main concepts that influenced the formation of cognitive poetics are identified; the relevant problems of cognitive studies of poetic and prose texts are analyzed. It’s  shown  that  it  is  necessary  to  further  consider  the  problem  of  identifying  dominant concepts of authors’ idiostyles describing cognitive mechanisms that underlie the semantic variability of individual concepts. The importance of using corpus methodology in the study of literary discourse in its synchronic and diachronic perspective is discussed.Conclusion. It is shown that, despite the fact that the author's creative consciousness has been  studied  intensively  and  for  a  long  time  in  Russian  cognitive  poetics,  there  are  still problems  that  need  further  consideration.  The  following  aspects  must  be  analyzed:  the criteria for choosing the method of modeling a literary concept, taking into consideration its type; the elaboration of uniform terminology in existing approaches; the development of the algorithms for describing the structure of literary concepts and identifying conceptual dominants  of  authors’  ideospheres.  A  conclusion  was  made  regarding  the  potential  of applying  corpus  research  methods  in  the  field  of  cognitive  poetics.  A  range  of  the  tasks related to the cognitive research of literary texts that could be solved by using statistical methods of corpus linguistics was determined.